Biomimetic Sequential Tautomerization/Dehydration/Addition Cascade Reactions: Facile Access to Proanthocyanidin Analogues Driven by Heating. Issue 9 (2nd March 2022) - Cui, Xin; Wang, Shuang; Lin, Junjie; Li, Jingpeng; Bai, Hairui; Wang, Xinghong; Huang, Chao
Abstract: An acid‐catalyzed, biomimetic cascades strategy for the synthesis of proanthocyanidin analogues is reported. The method lays in the structural transformations of 2‐hydroxychalcone strongly aﬀecting by pH and in situ generated flavylium salt intermediate could facile couping with π ‐nucleophile to form the proanthocyanidin‐type product. A proposed bioinspired cascade reaction pathway based on control experiments were also provided. These results are of interest for developing the total synthesis of proanthocyanidin natural products. Abstract : Acid‐driven, bioinspired cascade synthesis of proanthocyanidin analogues by heating has been achieved for the first time. A proposed bioinspired cascade reaction pathway based on control experiments were also provided. This strategy has important implications for developing the total synthesis of complex proanthocyanidin natural products.